Impact of ultrasonication, ultraviolet and atmospheric cold plasma processing on quality parameters of tomato-based beverage in comparison with thermal processing. (March 2019) - Mehta, Deepak; Sharma, Nitya; Bansal, Vasudha; Sangwan, Rajender S.; Yadav, Sudesh Kumar
Abstract: The aim of the study was to develop a tomato-based beverage and to investigate the effect of thermal (pasteurization) and non-thermal (ultrasonication, ultra-violet (UV), atmospheric cold plasma (ACP)) processing on the quality of a tomato-based beverage. The ultrasonication and ACP processing for 10 min put significant effect on L * and a * color values of the tomato beverage. All the processing techniques applied degraded ascorbic acid but maximum retention (95%) of ascorbic acid was found in ACP processed beverage. Furthermore, ACP processing of 10 min also had significant ( p ≥ 0.05) effect on bioactive compounds like chlorogenic acid, sinapic acid and gallic acid in comparison to thermal and other non-thermal processing. Moreover, ACP for 10 min and ultrasonication for 15 min was found equivalent to thermal processing in microbial reduction and ACP processing for 10 min was found equivalent to pasteurization in reduction of yeast and mold count. Both thermal and non-thermal processing had insignificant ( p ≥ 0.05) effects on pH, TSS and sugars of developed beverage. In summary, ACP processing for 10 min has emerged as the best processing method for retaining as well as improving the quality of the developed beverage. Highlights: Developed a tomato-based nutritional beverage Investigated effect of thermal and non-thermal processing on the quality of beverage ACP processed beverage retained maximum ascorbic acid. ACP processing for 10 min improved the quality of developed beverage.